Underwater non-dispersible concrete and its preparation process

By using specific anti-dispersant and fiber combinations in underwater non-dispersible concrete, a stable mesh structure and three-dimensional support net is formed, which solves the problem of insufficient dispersibility and mechanical strength of underwater concrete in deep-sea environments, and achieves high strength and excellent dispersive resistance.

CN116396033BActive Publication Date: 2025-03-07SICHUAN JINGYIDA ENG INSPECTION CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310263017.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-07
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The existing underwater non-dispersible concrete has poor dispersion resistance when the water depth exceeds 20m, and the water-land strength ratio is significantly reduced, which cannot meet the needs of high-strength underwater projects.

Method used

Polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate are used as anti-dispersants, combining basalt fibers and polyvinyl alcohol fibers to form a stable mesh structure and a three-dimensional support mesh, which significantly improves the anti-dispersion and mechanical strength of the concrete.

Benefits of technology

It significantly enhances the dispersion resistance and mechanical strength of underwater concrete, meets the needs of high-strength underwater engineering, and especially shows excellent performance in deep-sea environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004131998310000071
    Figure BDA0004131998310000071
  • Figure BDA0004131998310000081
    Figure BDA0004131998310000081
Patent Text Reader

Abstract

The present application relates to the technical field of concrete materials, and specifically discloses an underwater non-dispersible concrete and a preparation process thereof. The underwater non-dispersible concrete comprises the following raw materials: cement, mineral admixture, coarse aggregate, fine aggregate, water reducer, early strength agent, retarder, water, anti-dispersant and composite fiber, wherein the anti-dispersant mainly comprises polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate; the preparation process comprises the following steps: mixing cement, early strength agent, retarder and anti-dispersant with composite fiber to obtain mixture A; mixing coarse aggregate and fine aggregate and mineral admixture to obtain mixture B; mixing mixture A and mixture B, and then adding the water reducer mixed with water, mixing, and obtaining underwater non-dispersible concrete. The present application has the characteristics of improving the anti-dispersibility and compressive strength of underwater non-dispersible concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and more specifically, to an underwater non-dispersible concrete and a preparation process thereof. Background Art

[0002] With the development of society, the development of marine resources and the use and utilization of space below the surface water have become imperative. The application of concrete in underwater projects has become a new application technology, and underwater non-dispersible concrete has emerged. Compared with ordinary underwater concrete, underwater non-dispersible concrete overcomes the shortcomings of ordinary concrete such as poor water washing resistance, easy environmental pollution, and high requirements for special equipment. It can be directly poured in water and is not prone to dispersion and segregation. It is called "a brand-new, ideal, and epoch-making concrete" by domestic and foreign scholars.

[0003] Underwater non-dispersible concrete refers to a concrete material in which an appropriate amount of flocculant is added to ordinary concrete. The flocculant expands linearly in water, and the long-chain polymer is adsorbed on the surface of two or more colloidal particles. Therefore, the addition of flocculants increases the cohesiveness of concrete, which can reduce the loss of cement slurry caused by water scouring during underwater concrete pouring, thereby reducing the segregation phenomenon of light aggregate floating and heavy aggregate sinking. Thus, direct pouring of concrete in water is achieved, rainwater does not separate, cement does not lose, and it can self-level and self-compact when entering water, without vibration, and there is no environmental pollution to the construction water area. The concrete quality is uniform and reliable, which has a significant positive impact on the durability, workability and cost control of underwater concrete.

[0004] At present, my country's research on underwater non-dispersible concrete is suitable for the application of concrete below C30. When the water depth exceeds 20m, the concrete's anti-dispersion effect is poor, and the water-to-land strength ratio is significantly reduced, which does not meet the engineering requirements. With the deep-sea exploration and the construction of islands and reefs in the South China Sea, the engineering needs for good workability and high-strength underwater non-dispersible concrete are increasing, especially concrete above C40 is a major need for future underwater projects. Summary of the invention

[0005] In order to improve the anti-dispersion ability of concrete and improve the strength of underwater non-dispersion concrete, the present application provides an underwater non-dispersion concrete and a preparation process thereof.

[0006] In a first aspect, the present application provides an underwater non-dispersible concrete, which adopts the following technical solution:

[0007] An underwater non-dispersible concrete comprises the following raw materials in parts by weight:

[0008] 300-400 parts of cement, 60-90 parts of mineral admixture, 900-1000 parts of coarse aggregate, 550-650 parts of fine aggregate, 8-12 parts of water reducer, 3-5 parts of early strength agent, 1-3 parts of retarder, 150-200 parts of water, 5-15 parts of anti-dispersant and 8-10 parts of composite fiber, wherein the anti-dispersant mainly comprises polyacrylate, vinyl neodecanoate and pentasodium diethylenetriaminepentaacetate.

[0009] By adopting the above technical scheme, the anti-dispersion agent in the present application mainly includes polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate. Polyacrylate is used as a flocculant, has a long-chain molecule, forms a network structure with strong adsorption capacity, adsorbs cement, aggregate and other particles together, and improves the anti-dispersion of concrete. The addition of vinyl neodecanoate has an unsaturated double bond functional group at one end and a tertiary carbon polar structure at the other end. Its unsaturated group reacts with the unsaturated group in polyacrylate. The above vinyl neodecanoate is polymerized on the side chain of polyacrylate to form a more stable network structure, which can play a better anti-dispersion effect; and then the pentasodium diethylenetriamine pentaacetate is combined with the chelation effect of calcium and magnesium ions in cement to better adsorb cement and aggregate, further significantly improving its anti-dispersion effect, thereby reducing the loss of cement slurry due to hydraulic scouring during the pouring process, aggregate segregation and stratification and other problems resulting in low mechanical bearing capacity, and the anti-dispersion of the underwater concrete is significantly enhanced, and its strength is also significantly enhanced in combination with the effect of the early strength agent.

[0010] Optionally, the composite fiber is obtained by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:(2-2.5).

[0011] By adopting the above technical scheme, basalt fiber as an inorganic fiber has good mechanical properties, and polyvinyl alcohol fiber as an organic fiber can be well distributed in the concrete to form a three-dimensional random support network when added to concrete, and the organic fiber and concrete also have a certain bonding force. During the concrete molding process, the penetration of the fiber increases its internal binding force, making the concrete components more compact after molding, more conducive to the formation of stable floccules, and improving the anti-dispersion performance. In addition, the amino and carboxyl groups in the polyvinyl alcohol fiber and diethylenetriamine pentaacetic acid pentasodium act to construct a more stable network support structure, which improves the anti-dispersion performance while significantly improving the mechanical properties of the concrete itself, so that the underwater concrete has excellent anti-dispersion performance and higher mechanical strength.

[0012] Optionally, the anti-dispersant is obtained by mixing polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate in a mass ratio of 1:(0.5-0.6):(0.3-0.4).

[0013] Optionally, 1-2 parts by weight of divinyl sulfone are also added to the underwater non-dispersible concrete raw material.

[0014] By adopting the above technical solution, divinyl sulfone as a cross-linking agent is more conducive to the grafting of vinyl neodecanoate onto the branched chains of polyacrylate macromolecular polymers, forming branched chains with stronger polarity, which is more conducive to improving the water dispersibility of concrete.

[0015] Optionally, the mineral admixture is selected from silica fume, steel slag powder and phosphorus slag powder in a mass ratio of 1: (0.7-0.8): (1-1.2).

[0016] By adopting the above technical scheme, the addition of silica fume as a mineral admixture can enhance the strength of underwater non-dispersible concrete, the addition of steel slag powder can eliminate part of the alkali-aggregate reaction, and its addition can further improve the strength of concrete, phosphorus slag has high mineral activity, and the addition of phosphorus slag powder is beneficial to improve the quality of hydration products, thereby making the cement structure tighter, and it has high activity, and its secondary hydration reaction will increase the strength of cement, improve the interface structure and pore size distribution, so that the later strength of concrete is improved. The above-mentioned specific proportion of mineral admixtures is selected in this application, which not only improves the later strength of concrete, but also cooperates with early strength agent, which is beneficial to improve the early strength of concrete, overcomes the low early strength caused by phosphorus slag powder, and is beneficial to improve the overall strength of concrete.

[0017] Optionally, the water reducer is a naphthalene-based water reducer and a polycarboxylic acid water reducer in a mass ratio of 1:(2-3).

[0018] By adopting the above technical scheme, the compatibility of the anti-dispersant and the naphthalene-based water reducer is poor. The present application selects a specific anti-dispersant, and when compounded with the naphthalene-based water reducer and the polycarboxylic acid water reducer, the two are more compatible, and the final concrete has better anti-dispersibility and better overall performance.

[0019] Optionally, the cement is fast-hardening sulphoaluminate cement.

[0020] By adopting the above technical solution, when fast-hardening sulphoaluminate cement is used as cement, the strength of the final concrete produced is better and meets the demand for underwater high-strength concrete.

[0021] Optionally, the early strength agent is selected from one or more of triethanolamine and sulfate early strength agents;

[0022] The retarder is selected from one or more of sodium hexametaphosphate, calcium tartrate and sodium lignin sulfonate.

[0023] Optionally, the coarse aggregate is limestone crushed stone with a particle size of 5-20 mm;

[0024] The fine aggregate is machine-made sand with a fineness modulus of 2.4-2.8.

[0025] In a second aspect, the present application provides a process for preparing underwater non-dispersible concrete, which adopts the following technical solution: A process for preparing underwater non-dispersible concrete, comprising the following steps:

[0026] Mixing cement, early strength agent, retarder and anti-dispersion agent with composite fiber to obtain mixture A;

[0027] Mixing the coarse aggregate, the fine aggregate and the mineral admixture to obtain a mixture B;

[0028] Mixture A and mixture B are mixed, and then a water reducing agent mixed with water is added and mixed to obtain underwater non-dispersible concrete.

[0029] By adopting the above technical solution, the preparation process of the present application is simple and convenient, and can be easily promoted on a large scale.

[0030] Optionally, 1-2 parts by weight of divinyl sulfone is also added to the underwater non-dispersible concrete raw material;

[0031] After adding the mixture of water reducing agent and water, divinyl sulfone is added and mixed to obtain underwater non-dispersible concrete.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The anti-dispersion agent of the present application contains vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate, which further significantly improves its anti-dispersion effect, thereby reducing the loss of cement slurry due to hydraulic scouring during the pouring process, aggregate segregation and stratification, and other problems that lead to low mechanical bearing capacity. The anti-dispersion property of the underwater concrete is significantly enhanced, and its strength is also significantly enhanced in combination with the effect of the early strength agent;

[0034] 2. One end of the vinyl neodecanoate in the anti-dispersant of the present application has an unsaturated double bond functional group, and the other end has a tertiary carbon polar structure. The unsaturated group reacts with the unsaturated group in the polyacrylate, and the above-mentioned vinyl neodecanoate is polymerized on the side chain of the polyacrylate to form a more stable network structure, so that it can have a better anti-dispersion effect; and then cooperate with the chelation effect of pentasodium diethylenetriamine pentaacetate and calcium and magnesium ions in cement to better adsorb cement and aggregate; 3. The inorganic basalt fiber in the present application improves the mechanical properties of concrete, and the organic polyvinyl alcohol fiber can be well distributed in the concrete when added to the concrete to form a three-dimensional random support network, so that the concrete components are more compact after molding, and the anti-dispersion performance is improved. In addition, the polyvinyl alcohol fiber reacts with the amino and carboxyl groups in pentasodium diethylenetriamine pentaacetate. Thereby, a more stable network support structure is constructed, and the mechanical properties of the concrete itself are significantly improved while the anti-dispersion performance is improved. The underwater concrete obtained has excellent anti-dispersion performance and higher mechanical strength; 4. The mineral admixtures in this application are selected from silica fume, steel slag powder and phosphorus slag powder in specific proportions. The addition of steel slag powder can eliminate part of the alkali aggregate reaction, and its addition can further improve the strength of the concrete. The addition of phosphorus slag powder and its secondary hydration reaction will increase the strength of cement, improve the interface structure and pore size distribution, and improve the later strength of the concrete. The above-mentioned specific proportion of mineral admixtures are selected in this application, which not only improves the later strength of the concrete, but also cooperates with the early strength agent to improve the early strength of the concrete, overcomes the low early strength caused by phosphorus slag powder, and is beneficial to improve the overall strength of the concrete. DETAILED DESCRIPTION

[0035] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0036] In the following examples, the cement used was fast-hardening sulphoaluminate cement grade 42.5;

[0037] The naphthalene-based water reducer uses UNF-5 naphthalene-based water reducer;

[0038] The polycarboxylate water reducer is Viscocrete 3000 polycarboxylate high-efficiency water reducer;

[0039] The coarse aggregate is limestone crushed stone with a particle size of 5-20mm;

[0040] The fine aggregate is machine-made sand with a fineness modulus of 2.4-2.8.

[0041] Example 1

[0042] A process for preparing underwater non-dispersible concrete comprises the following steps:

[0043] S1, 350 kg of cement, 4 kg of early strength agent, 2 kg of retarder and 10 kg of anti-dispersant are mixed with 9 kg of composite fiber to obtain a mixture A;

[0044] S2, mixing 950 kg of coarse aggregate, 600 kg of fine aggregate and 75 kg of mineral admixture to obtain mixture B;

[0045] S3. Mix mixture A and mixture B, then add 10 kg of water reducer mixed with 180 kg of water, and mix to obtain underwater non-dispersible concrete.

[0046] Among them, the early strength agent is triethanolamine and sulfate early strength agent with a mass ratio of 1:1;

[0047] The retarder is sodium hexametaphosphate and calcium tartrate in a mass ratio of 1:1;

[0048] The anti-dispersion agent is obtained by mixing polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate in a mass ratio of 1:0.5:0.3;

[0049] The composite fiber is obtained by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:2.2;

[0050] Mineral admixtures are selected from silica fume, steel slag powder and phosphorus slag powder in a mass ratio of 1:0.8:1;

[0051] The water reducer is a mixture of naphthalene water reducer and polycarboxylic acid water reducer in a mass ratio of 1:2.5.

[0052] Example 2

[0053] A process for preparing underwater non-dispersible concrete comprises the following steps:

[0054] S1, 300 kg of cement, 3 kg of early strength agent, 1 kg of retarder and 5 kg of anti-dispersant are mixed with 8 kg of composite fiber to obtain a mixture A;

[0055] S2, mixing 900 kg of coarse aggregate, 550 kg of fine aggregate and 60 kg of mineral admixture to obtain mixture B;

[0056] S3. Mix mixture A and mixture B, then add 8 kg of water reducer mixed with 150 kg of water, and mix to obtain underwater non-dispersible concrete.

[0057] Among them, triethanolamine early strength agent is used as early strength agent;

[0058] Sodium hexametaphosphate is used as retarder;

[0059] The anti-dispersion agent is obtained by mixing polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate in a mass ratio of 1:0.5:0.3;

[0060] The composite fiber is obtained by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:2;

[0061] Mineral admixtures are selected from silica fume, steel slag powder and phosphorus slag powder in a mass ratio of 1:0.7:1;

[0062] The water reducer is a mixture of naphthalene water reducer and polycarboxylic acid water reducer in a mass ratio of 1:2.

[0063] Example 3

[0064] A process for preparing underwater non-dispersible concrete comprises the following steps:

[0065] S1, 400 kg of cement, 5 kg of early strength agent, 3 kg of retarder and 15 kg of anti-dispersant are mixed with 10 kg of composite fiber to obtain a mixture A;

[0066] S2, mixing 1000 kg of coarse aggregate, 650 kg of fine aggregate and 90 kg of mineral admixture to obtain mixture B;

[0067] S3. Mix mixture A and mixture B, then add 12 kg of water reducer mixed with 200 kg of water, and mix to obtain underwater non-dispersible concrete.

[0068] Among them, the early strength agent is a sulfate early strength agent; the retarder is calcium tartrate;

[0069] The anti-dispersion agent is obtained by mixing polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate in a mass ratio of 1:0.6:0.4;

[0070] The composite fiber is obtained by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1:2.5;

[0071] Mineral admixtures are selected from silica fume, steel slag powder and phosphorus slag powder in a mass ratio of 1:0.8:1.2;

[0072] The water reducer is a mixture of naphthalene water reducer and polycarboxylic acid water reducer in a mass ratio of 1:3.

[0073] Example 4

[0074] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that 1 kg of divinyl sulfone is added after adding a mixture of a water reducer and water, and the mixture is mixed to obtain underwater non-dispersible concrete.

[0075] Example 5

[0076] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that 2 kg of divinyl sulfone is added after adding a mixture of a water reducer and water, and the mixture is mixed to obtain underwater non-dispersible concrete.

[0077] Example 6

[0078] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that an equal amount of polyvinyl alcohol fibers is replaced by polyethylene fibers.

[0079] Example 7

[0080] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that the mineral admixtures are silica fume and steel slag powder with a mass ratio of 1:0.8.

[0081] Example 8

[0082] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that the mineral admixtures are silica fume and phosphorus slag powder in a mass ratio of 1:1.

[0083] Example 9

[0084] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that the mineral admixtures are silica fume and fly ash in a mass ratio of 1:1.

[0085] Example 10

[0086] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that an equal amount of cement is replaced with 42.5 grade ordinary Portland cement.

[0087] Comparative Example 1

[0088] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that vinyl neodecanoate and pentasodium diethylenetriaminepentaacetate are not added to the anti-dispersant.

[0089] Comparative Example 2

[0090] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that vinyl neodecanoate is not added to the anti-dispersant.

[0091] Comparative Example 3

[0092] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that pentasodium diethylenetriamine pentaacetate is not added to the anti-dispersant.

[0093] Comparative Example 4

[0094] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that an equal amount of pentasodium diethylenetriaminepentaacetate is replaced by sodium ferric ethylenediaminetetraacetate in the anti-dispersant.

[0095] Comparative Example 5

[0096] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that an equal amount of composite fibers is replaced by basalt fibers.

[0097] Comparative Example 6

[0098] A process for preparing underwater non-dispersible concrete is carried out according to the method in Example 1, except that an equal amount of composite fibers is replaced by polyvinyl alcohol fibers.

[0099] Performance Testing

[0100] The underwater non-dispersible concrete prepared in the embodiments and comparative examples was characterized in terms of anti-dispersion and mechanical strength. The anti-dispersion was characterized by measuring the weight difference of the underwater non-dispersible concrete before and after pouring in water by a weighing method, and the test results were shown in Table 1 below. In addition, the compressive strength of the underwater non-dispersible concrete at different ages was tested with reference to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50081-2002), and the compressive strength of the underwater concrete at 7d and 28d was measured, respectively. The results are shown in Table 2 below.

[0101] Table 1:

[0102]

[0103] Table 2:

[0104]

[0105]

[0106] Referring to the test results in Table 1 and Table 2 above, it can be seen that the underwater non-dispersible concrete prepared in Examples 1-5 of the present application has excellent anti-dispersion performance and also has excellent mechanical strength performance, especially excellent underwater mechanical strength performance, with an early strength of greater than 40 MPa, which meets the current demand for underwater high-strength concrete.

[0107] Combining the test results of Example 1 with those of Example 4 and Example 5, it can be seen that when divinyl sulfone is added to the concrete raw materials, the anti-dispersion and mechanical properties of the concrete are improved; referring to the test results of Example 1 and Example 6, when the polyvinyl alcohol fiber in the composite fiber is replaced by polyethylene fiber in equal amounts, its anti-dispersion performance is significantly reduced, and the underwater mechanical strength is also reduced. This may be because the hydroxyl group and double bond functional groups in the polyvinyl alcohol fiber react with the substances in the anti-dispersion agent, and the network structure formed is more stable and the anti-dispersion performance is better;

[0108] Referring to the test results of Example 1 and Examples 7-9, it can be seen that when only silica fume and steel slag powder or phosphorus slag powder are selected as mineral admixtures, or when silica fume is mixed with other admixtures such as fly ash, its anti-dispersion property is reduced, and its mechanical properties are also reduced. When steel slag powder is added but phosphorus slag powder is not added in Example 7, its early strength is larger, while the increase in later strength is smaller; when phosphorus slag powder is added but steel slag powder is not added, its early strength is smaller, while the increase in later strength is larger. When the above two admixtures are not added, the mechanical properties are significantly reduced. Combined with the test results of Example 10, it can be seen that cement selected from sulphoaluminate cement has better underwater mechanical properties than ordinary silicate cement.

[0109] Referring to the test results of Example 1 and Comparative Example 1, it can be seen that when vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate are not added to the anti-dispersion agent, its anti-dispersion property is poor and the mechanical properties are significantly reduced; when vinyl neodecanoate or pentasodium diethylenetriamine pentaacetate is not added in Comparative Examples 2 and 3, its performance is improved but still poor; referring to Comparative Example 4, when pentasodium diethylenetriamine pentaacetate is replaced by sodium ferric ethylenediaminetetraacetate in equal amounts, its anti-dispersion property and mechanical properties are poor; when the composite fiber is replaced by polyvinyl alcohol fiber or basalt fiber in equal amounts in Comparative Examples 5 and 6, although the mechanical properties are better when replaced by basalt fiber, its anti-dispersion property is poor, and when the two are added together, they have excellent anti-dispersion property and excellent mechanical properties.

[0110] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An underwater non-dispersible concrete, characterized in that: It includes the following raw materials in parts by weight: 300-400 parts of cement, 60-90 parts of mineral admixture, 900-1000 parts of coarse aggregate, 550-650 parts of fine aggregate, 8-12 parts of water reducer, 3-5 parts of early strength agent, 1-3 parts of retarder, 150-200 parts of water, 5-15 parts of anti-dispersant and 8-10 parts of composite fiber; The composite fiber is obtained by mixing polyvinyl alcohol fiber and basalt fiber in a mass ratio of 1: (2-2.5); The anti-dispersion agent is obtained by mixing polyacrylate, vinyl neodecanoate and pentasodium diethylenetriamine pentaacetate in a mass ratio of 1: (0.5-0.6): (0.3-0.4); the mineral admixture is selected from silica fume, steel slag powder and phosphorus slag powder in a mass ratio of 1: (0.7-0.8): (1-1.2).

2. The underwater non-dispersible concrete according to claim 1, characterized in that: The underwater non-dispersible concrete raw material further contains 1-2 parts by weight of divinyl sulfone.

3. The underwater non-dispersible concrete according to claim 1, characterized in that: The water reducer is a naphthalene water reducer and a polycarboxylic acid water reducer in a mass ratio of 1: (2-3); the cement is a fast-hardening sulphoaluminate cement.

4. The underwater non-dispersible concrete according to claim 1, characterized in that: The early strength agent is selected from one or more of triethanolamine and sulfate early strength agents; The retarder is selected from one or more of sodium hexametaphosphate, calcium tartrate and sodium lignin sulfonate.

5. The underwater non-dispersible concrete according to claim 1, characterized in that: The coarse aggregate is limestone crushed stone with a particle size of 5-20 mm; The fine aggregate is machine-made sand with a fineness modulus of 2.4-2.

8.

6. The process for preparing underwater non-dispersible concrete according to claim 1, characterized in that: Mixing cement, early strength agent, retarder and anti-dispersion agent with composite fiber to obtain mixture A; Mixing the coarse aggregate, the fine aggregate and the mineral admixture to obtain a mixture B; Mixture A and mixture B are mixed, and then a water reducing agent mixed with water is added and mixed to obtain underwater non-dispersible concrete.

7. A process for preparing underwater non-dispersible concrete according to claim 6, characterized in that: The underwater non-dispersible concrete raw material further comprises 1-2 parts by weight of divinyl sulfone; After adding the mixture of water reducing agent and water, divinyl sulfone is added and mixed to obtain underwater non-dispersible concrete.

Citation Information

Patent Citations

  • 3D printing cement-based material used for underwater construction and preparation method thereof

    CN107311561A

  • Fiber reinforced concrete raw material, fiber reinforced concrete and preparation method and application thereof

    CN110330273A

  • Preparation method of special concrete regulator

    CN110903050A